Cognitive effects of altitude exposure - Burtscher, Johannes; Gassmann, Max; Ehrenreich, Hannelore; Hüfner, Katharina; Kopp, Martin; Burtscher, Martin (Journal of travel medicine, 2024)
Almost 85% out of ~500 million people residing above 1500 m are living at moderate altitudes, i.e. between 1500 and 2500 m, and millions of tourists annually travel to moderate altitudes for sight-seeing, mountaineering or skiing. [1] Although the impact of prolonged altitude exposure (hypobaric hypoxia) on cognitive performance is well investigated, only a few studies have explicitly compared the cognitive effects of moderate (1500-2500 m) and high altitude (>2500 m). Thus, the influence and possibly distinct effects of different altitude levels are insufficiently understood and a common source of misinterpretation. This is due to the assumption that cognitive deficits observed at very high (3500-5500 m) and extreme (>5500 m) altitudes increase in a linear fashion starting from sea level up to the highest terrestrial altitudes. Accordingly, the exposure to moderate altitude could be assumed to be associated with mild cognitive risks, which is relevant for the huge number of moderate altitude residents and sojourners. However, experimental data do not support such a linear relationship, and this is in line with the non-linear shape of the oxygen-haemoglobin dissociation curve (ODC). The ODC is characterized by an only slight decrease of arterial oxygen saturation (SaO2) up to an altitude of ~2500 m (and an associated arterial partial pressure of oxygen, PaO2, of ~60 mmHg), followed by a steep decline of SaO2 and continuously dropping PaO2 with increasing altitude. Here, we present the hypothesis that the slight decline of SaO2 during prolonged exposure to moderate altitude, in combination with additional repeated hypoxia-amplifying stimuli (e.g. during sleep or exercise), facilitates physiological responses to hypobaric hypoxia that may even protect from cognitive impairment in healthy people (Fig. 1). With the steeper decline of SaO2 in higher altitudes, the physiological adaptive capacities of the central nervous system and relevant other systems (in particular the cardiovascular and respiratory systems) may be overwhelmed, resulting in increasingly more severe cognitive impairment.
Gesehen am 16.10.2024